Epidemiological profiling of fatal road crashes in Puducherry, South Coastal India - N Anand; Biju Soman; Manivel Prakash (Wolters Kluwer Medknow Publications, 2021)
Road crash fatalities form leading cause of deaths in India. Streamlining road crash data systems are essential for building robust prevention strategies. This study explores epidemiological profile of fatal road crashes in a south Indian urban setting. Between April and June 2019, secondary data on fatal road crashes in Puducherry district for 3-year period (2016, 2017, and 2018) were accessed from traffic police records and analyzed. Raw data accessed in descriptive format was converted to analyzable objective format by self-developed data extraction template. 154 fatal crashes happened in Puducherry during this period. Most victims were males (85.7%), in productive age group (41.5%), with higher rates in monsoon and winter seasons (35.1% each), during evening-to-night hours (41.6%), and during weekends (42%). Most offenders (91.2%) were men, elder than victims, with heavy motor vehicles (91.2%) being the culprit vehicle. Rash driving led to most deaths (53.2%).